Gestational perturbation of homocysteine metabolism reduces Spina bifida prevalence in Osun State, Nigeria - Akanni, Emmauel Olufemi; Adedeji, Adebayo Lawrence; Oyinlola, Oyindamola Nike; Azeez, Raufu Taiwo; Akinbo, David Bolaji (Asian Journal of Medical Sciences, 2020)
Background: Elevated maternal homocysteine concentration has been described as a consequence of disruptions in methionine and/or folate metabolism which is associated with adverse outcomes and several obstetric complications inclusive of neural tube defects in offspring such as spina bifida, preeclampsia and spontaneous abortion. Aims and Objectives: The current study investigated the influence of maternal homocysteine metabolism in singleton pregnant women on the prevalence of Spina bifida in Osun State. Materials and Methods: Sixty (60) subjects attending Ladoke Akintola University of Technology Teaching Hospital and State Specialist Hospital in Osogbo, Osun State were randomly recruited for the study which spanned from January 2018 through April 2018 involving 30 apparently healthy singleton pregnant women classified according to gestational age and 30 apparently healthy age- and socio-economic status-matched non-pregnant women as controls. Haematocrit, haemoglobin concentration, total white cell count as well as the levels of homocysteine concentration were assessed. Results: Haematocrit and haemoglobin concentration in all three trimesters were significantly (p< 0.05) decreased when compared with their non-pregnant counterparts. There was however a significant (p< 0.05) increase in the expression of circulating homocysteine in all three trimesters compared to the control group, and an observed steady decline in the second trimester through the third trimester. Conclusion: These findings therefore imply that gestational perturbation of homocysteine metabolism may contribute to reduced risk of spina bifida in Osun State, Nigeria.